Replisome genes regulation by antitumor miR‐101‐5p in clear cell renal cell carcinoma. Issue 4 (22nd February 2020) - Yamada, Yasutaka; Nohata, Nijiro; Uchida, Akifumi; Kato, Mayuko; Arai, Takayuki; Moriya, Shogo; Mizuno, Keiko; Kojima, Satoko; Yamazaki, Kazuto; Naya, Yukio; Ichikawa, Tomohiko; Seki, Naohiko
Abstract: Analysis of microRNA (miRNA) regulatory networks is useful for exploring novel biomarkers and therapeutic targets in cancer cells. The Cancer Genome Atlas dataset shows that low expression of both strands of pre‐ miR‐101 ( miR‐101‐5p and miR‐101‐3p ) significantly predicted poor prognosis in clear cell renal cell carcinoma (ccRCC). The functional significance of miR‐101‐5p in cancer cells is poorly understood. Here, we focused on miR‐101‐5p to investigate the antitumor function and its regulatory networks in ccRCC cells. Ectopic expression of mature miRNAs or siRNAs was investigated in cancer cell lines to characterize cell function, ie, proliferation, apoptosis, migration, and invasion. Genome‐wide gene expression and in silico database analyses were undertaken to predict miRNA regulatory networks. Expression of miR‐101‐5p caused cell cycle arrest and apoptosis in ccRCC cells. Downstream neighbor of son ( DONSON ) was directly regulated by miR‐101‐5p, and its aberrant expression was significantly associated with shorter survival in propensity score‐matched analysis ( P  = .0001). Knockdown of DONSON attenuated ccRCC cell aggressiveness. Several replisome genes controlled by DONSON and their expression were closely associated with ccRCC pathogenesis. The antitumor miR‐101‐5p / DONSON axis and its modulated replisome genes might be a novel diagnostic and therapeutic target for ccRCC. Abstract : MicroRNA‐101‐5p expression was downregulated in clear cell renal cell carcinoma (ccRCC) tissues and functioned as tumor‐suppressive microRNA. MicroRNA‐101‐5p directly regulated DONSON, which was highly expressed in ccRCC and sunitinib‐resistant RCC tissues. DONSON and other replisome‐related genes have a potential to be diagnostic and therapeutic targets in ccRCC.